A survey on video classification using action recognition - Andrew, Caleb; Fiona, Rex (International Journal of Engineering and Technology, 2018)
The growth in multimedia technology have resulted in producing a variety of videos every day. These videos should be classified in order to help people identify the correct video which they search for when needed. The video classification problem can be said as a probabilistic data classification problem which falls as a subcategory of the machine learning technique. Classification helps in indexing, analyzing, searching etc. A survey has been made on the present technologies that are used for video classification. Various techniques used for video classification such as Multiple Instance Learning (MIL), Conditional Random Field (CRFs) and classifying based on the action and gesture are studied.Â